Hubungan Kecerdasan Visual Spasial dan Kecerdasan Kinestetik dengan Hasil Belajar Matematika Siswa SMP Negeri 184 Jakarta - Ramadhania, Yuka; Nuriadin, Ishaq; Maarif, Samsul (International Journal of Progressive Mathematics Education, 2023)
The purpose of this study was to determine the relationship between Visual Spatial Intelligence and Kinesthetic Intelligence with Mathematics learning outcomes for junior high school students. The method used is a survey method with a correlation technique that is looking for a relationship between Visual Spatial Intelligence and Kinesthetic Intelligence with Mathematics learning outcomes through a survey using Google Forms. This research was conducted at SMP Negeri 184 Jakarta and a sample of 100 students was taken. The sampling technique used in this research is purposive random sampling. The research instrument was a questionnaire and a test of learning outcomes. The results of the study show the results of the first hypothesis that there is no significant relationship between Visual Spatial Intelligence and student learning outcomes. The second hypothesis is that there is a significant relationship between Kinesthetic Intelligence and student learning outcomes. The third hypothesis is that there is no simultaneous relationship between Visual Spatial Intelligence and Kinesthetic Intelligence and student learning outcomes.